Single-entity electrochemistry: Diffusion-controlled transport of an analyte inside a particle - Le, H; Lin, C; Kätelhön, E; Compton, R (Elsevier, 2018)
Recent progress in nanoparticle electrochemistry has enabled the detection of individual nanoparticles and the characterisation of nanoparticle populations. The nano-impact technique, in which individual nanoparticles diffusively reach and react at an electrode, has advanced to allow exciting insights into reaction mechanisms from inference of the progress of the reaction of an individual nanoparticle as reflected in the electrode current-time response. This work characterises the diffusion-limited depletion of an analyte inside a nanoparticle which is initially doped with this analyte and, upon impact at the electrode, may deform, adsorb, and react. Two different theoretical models are contrasted and we reveal that key physical quantities such as the contact area of the particle and electrode can be extracted from experimental data in favourable cases. In addition, a dimensional analysis of the theoretical model is presented which simplifies the analysis of experimental data by reducing the number of required fitting parameters.